EFEKTIVITAS PENANGANAN KASUS KEKERASAN SEKSUAL TERHADAP PEREMPUAN PERSPEKTIF MAQASID ASY SYARIAH DI KEPOLISIAN RESOR DEMAK - Dania Saferina Ifada (Program Studi Hukum Keluarga Islam, 2023)
Acts of sexual violence experienced by women in Indonesia still show high numbers. This figure is only a handful of the many cases of sexual violence because in reality there are still many women victims of sexual violence who do not report it to the police or service agencies such as the National Commission on Violence Against Women. This research was conducted with the aim of finding out how effective the handling of cases of sexual violence against women is, to find out what are the inhibiting factors and find out the solutions that can be used to prevent cases of sexual violence against women and to find out the effectiveness of handling sexual violence against women from the maqasid Asy-Syariah perspective. The method used in this study was a field search method. In this study, the researcher obtained information from the field and signed various informants in order to obtain correct results. The subjects of this research were the Demak Resort Police and the Women's and Children's Services Unit in providing explanations about women who were victims of sexual violence. The data analysis process was carried out by analyzing the effectiveness of the handling of cases of sexual violence against women by the Demak Resort Police in reducing the number of sexual violence against women in the city of Demak, analyzing the inhibiting factors and providing solutions in handling cases of sexual violence against women as well as the effectiveness of handling cases of sexual violence towards women from the maqasid asy-shariah perspective. Based on the findings and results of the analysis, it was found that the Demak Resort Police had made every effort to reduce the number of sexual violence against women. there are obstacles in dealing with cases of sexual violence against women such as limited funds, lack of human resources, limited facilities, and the presence of victims' families who do not want to report incidents of violence experienced by victims. The handling of the Demak Resort Police in dealing with cases of sexual violence from the maqasid asy-shari'ah perspective must be in line with the objectives of Islamic law, namely the protection of life, mind, lineage and property. In Islam, women must be treated special and get protection from a man. This is where a woman has the right to get self-protection, get respect and get proper treatment from a man so that women are not easy to become victims of sexual violence.